Pengaruh Pinjaman Online terhadap Kondisi Ekonomi Mahasiswa - Yunita Ria Anjani; Natasya Kamila; M. Fauzan Nawawi Ali (INDO PUBLISHING, 2026)
The rapid development of financial technology (fintech) has increased the accessibility of online lending services among various groups, including university students. The ease of access, fast disbursement process, and minimal requirements have made online loans an alternative source of funding for students facing financial difficulties. This study aims to analyze the influence of online loans on students’ economic conditions, identify the factors affecting their usage, examine the resulting impacts, and propose possible solutions to minimize associated risks. This research employs a descriptive qualitative approach using a literature review method by examining various relevant scientific articles, journals, and academic references. The findings indicate that the use of online loans among students is primarily influenced by economic needs, low levels of financial literacy, consumptive lifestyles, and the convenience of digital financial services. Although online loans provide benefits such as quick access to funds for urgent needs, their negative impacts tend to be more dominant, including increased debt burdens, poor financial management, consumptive behavior, and psychological stress. Therefore, efforts to address these issues should focus on improving financial literacy, strengthening awareness of the risks associated with online lending, promoting responsible financial behavior, providing safer financing alternatives, and enhancing the role of higher education institutions in offering financial guidance and support. Through these measures, students are expected to make more informed financial decisions and reduce their dependence on online lending services.